SIMANJA ESEMANIS ALTERNATIF MODEL PEMBELAJARAN BLENDED LEARNING DI SMA NEGERI 1 SALAMAN - IMAM TOIFUR (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
This best practice writing aims to describe: 1) the effectiveness of the blended learning model using Simanja Esemanis on the polynomial division material; 2) the impact of the blended learning model using Simanja Esemanis on the polynomial division material. The subjects of this best practice writing are 36 students of class XI MIPA 1 SMA Negeri 1 Salaman for the 2021/2022 academic year. The best practice writing uses a descriptive method. Collecting information on student activities through documentation and student learning outcomes using tests. The strategy used is blended learning with Simanja Esemanis. The implementation of the blended learning model using Simanja Esemanis can increase the effectiveness of learning mathematics. The average value of learning outcomes before the application of blended learning was 76.43 (enough category) and increased to 82.86 (good category) after the application of blended learning. The percentage of completeness also increased from 68.57% (classical incomplete) to 82.86% (classical complete). In addition, the implementation of the blended learning model with Simanja Esemanis also increases the activeness of students. This can be observed from the timeliness in collecting assignments given online and always filling out the attendance list according to learning hours. ABSTRAKPenulisan best practice ini bertujuan untuk mendeskripsikan: 1) efektivitas model pembelajaran blended learning menggunakan Simanja Esemanis pada materi pembagian polinomial; 2) dampak model pembelajaran blended learning menggunakan Simanja Esemanis pada materi pembagian polinomial. Subjek penulisan best practice ini adalah peserta didik kelas XI MIPA 1 SMA Negeri 1 Salaman Tahun Pelajaran 2021/2022 yang berjumlah 36. Penulisan best practice menggunakan metode deskriptif. Pengumpulan informasi aktivitas peserta didik melalui dokumentasi dan hasil belajar peserta didik dengan menggunakan tes. Strategi yang digunakan adalah pembelajaran blended learning dengan Simanja Esemanis. Implementasi model pembelajaran blended learning dengan menggunakan Simanja Esemanis dapat meningkatkan efektivitas pembelajaran matematika. Rata-rata nilai hasil belajar sebelum penerapan blended learning 76,43 (kategori cukup) meningkat menjadi 82,86 (kategori baik) setelah penerapan blended learning. Persentase ketuntasan juga meningkat dari 68,57% (tidak tuntas klasikal) menjadi 82,86% (tuntas klasikal). Selain itu, implementasi model pembelajaran blended learning dengan Simanja Esemanis juga meningkatkan keaktifan peserta didik. Hal ini bisa diamati dari ketepatan waktu dalam pengumpulan tugas yang diberikan secara online dan selalu mengisi daftar hadir sesuai jam pembelajaran.